Effect of thermal annealing treatments on the optical and electrical properties of aluminum-doped, amorphous, hydrogenated silicon carbide thin films - Sánchez Sovero, Luis Francisco (2019)
This research was funded by the National Council for Science, Technology and Technological Innovation (CONCYTEC) of the Pontificia Universidad Catholica del Perú (PUCP).